Selective oxidation of ethane over Mo-V-Al-O oxide catalysts: insight to the factors affecting the selectivity of ethylene and acetic acid and structure-activity correlation studies - Sankaranarayanan, T. M.; Ingle, Rohit H.; Gaikwad, T. B.; Lokhande, S. K.; Raja, T.; Devi, R. N.; Ramaswamy, V.; Manikandan, Palanichamy (Catalysis Letters, 2008)
Catalysts of general formula, MoVAlOx were prepared with the initial elemental composition of 1:0.34:0.167 (Mo:V:Al) at a pH value in the range of 1-4. The elemental analysis showed that the final composition of the catalysts is pH dependant. The performance of the catalysts was tested for selective oxidation of ethane to give ethylene and acetic acid. While all of them were active for ethane oxidation with a moderate conversion, the catalyst prepared at pH 2 showed a highest activity with 23% ethane conversion and a combined selectivity of 80.6% to ethylene and acetic acid. The catalyst prepared at pH 4 was least selective to ethylene and acetic acid. Various techniques like powder XRD, SEM, Raman, UV-Vis and EPR were used to characterize the catalysts and to identify the active phases responsible for the selective oxidation of ethane. The powder XRD data showed that the catalysts prepared at pH 1 and 2 contain mainly of MoO3 and MoV2O8 along with traces of Mo4O11. The amount of MoO3 was slightly higher in the catalyst prepared at pH 1. However, the catalyst prepared at pH 3 contains mainly of MoV2O8 with no trace of MoO3. The catalyst prepared at pH 4 showed V2O5 as the major phase along with MoVAlO4 phase. The Raman data corroborated the XRD results. EPR and UV-Vis studies indicated the presence of traces of V-4 in pH 1 and 2 catalysts and significant amount of Mo5+ in all the catalysts. Thus, the high activity and selectivity to ethylene and acetic acid are attributed to the presence of MoV2O8 phase and other reduced species like Mo4O11 phase supported on MoO3. The presence of V and Mo ions in a partially reduced form seems to play a crucial role in the selective oxidation of ethane.
Keywords: Acetic acid; ethane; Ethylene; mixed metal oxide; Selective oxidation

Copper-based catalysts for water gas shift reaction: influence of support on their catalytic activity - Pradhan, S.; Reddy, A. Satyanarayana; Devi, R. N.; Chilukuri, Satyanarayana V. (Catalysis Today, 2009)
Three copper containing catalysts supported on ceria and mixed oxides of ceria with zirconia and titania were prepared by co-precipitation method and their catalytic activity was tested for water gas shift (WGS) reaction. High surface area (>100m(2)/g) mixed oxides were obtained following the present method of preparation. The catalysts were characterized by XRD, H(2)-temperature programmed reduction (TPR), UV-vis and XPS. Catalytic activity was evaluated for water gas shift reaction in the 200-400 degrees C temperature range, The gas hourly space velocity was varied from 5000 to 25,000h(-1) for better evaluation and comparison of their performance. The effect of CO(2) in the feed gas mixture on the WGS activity of these catalysts was also studied. Among the three catalysts studied, CuO-CeO(2)-ZrO(2) mixed oxide shows better activity, implying the influence of support. Characterization of the catalysts after WGS reaction was also carried out in order to investigate structure-property correlation. (c) 2008 Elsevier B.V. All rights reserved.
18th National Symposium and Indo-US Seminar on Catalysis, Indian Inst Petroleum, Dehradun, INDIA, APR 16-18, 2007
Keywords: ceria; Ceria-titania; Ceria-zirconia; Co-precipitation; Copper; Water gas shift

Bifunctional oxygen reduction and evolution activity in brownmillerites Ca2Fe(1- x)CoxO5 - Thundiyil, S.; Kurungot, S.; Devi, R. N. (ACS Omega, 2019)
State-of-the-art catalysts for oxygen reduction and evolution reactions (ORR and OER), which form the basis of advanced fuel cell applications, are based on noble metals such as Pt and Ir. However, high cost and scarcity of noble metals have led to an increased demand of earth-abundant metal oxide catalysts, especially for bifunctional activity in ORR and OER. The fact that Pt and Ir or C, the cost-effective alternatives suggested, do not display satisfactory bifunctional activity has also helped in turning the interest to metal oxides which are stable under both ORR and OER conditions. Brownmillerite A2B2O5 type oxides are promising as bifunctional oxygen electrocatalysts because of intrinsic structural features, viz., oxygen vacancy and catalytic activity of the B-site transition metal. In this study, Co-doped Ca2Fe2O5 compounds are synthesized by the solid state method and structurally analyzed by Rietveld refinement of powder X-ray diffraction data. The compound Ca2Fe2O5, crystallizing in the Pcmn space group has alternative FeO4 tetrahedral and FeO6 octahedral layers. Its Co-doped analogue, Ca2Fe1.75Co0.25O5, also crystallizes in the same space group with both tetrahedral and octahedral Fe positions substituted with Co. However, Ca2FeCoO5 in the Pbcm space group shows interlayer ordering with Co-rich octahedra connected to Fe-rich tetrahedra and vice versa. Oxygen bifunctional activities of these catalysts are monitored by rotating disc electrode and rotating ring disc electrode techniques in alkaline media. A close analysis of the ORR and OER was conducted through comparison of various parameters such as onset potential, current density, halfwave potential, and other kinetic parameters, which suggests that the presence of Co in the B site aids in achieving better bifunctional activity and bulk conductivity. In addition, Co(II)/Co(III) redox systems and their comparative concentrations also play a decisive role in enhancing the activity.

Squaraine-linked metalloporphyrin two-dimensional polymer photocatalyst for hydrogen and oxygen evolution reactions - Ranjeesh, K. C.; George, L.; Wakchaure, V. C.; Goudappagouda; Devi, R. N.; Babu, S. S. (Chemical Communications, 2019)
Efficient water splitting photocatalysts are an energetically demanding and cost-effective method for generating renewable energy. Significant research has been reported to advance this approach. However, the use of organic photocatalysts and the presence of residual catalysts trapped in the porous frameworks present major concerns about the efficiency of this strategy. Herein, we report the photocatalytic evolution of H2 and O2 by a multi-hydroxyl group-decorated metalloporphyrin-based two-dimensional catalyst developed via metal catalyst-free synthetic route. Though metalloporphyrins have long been used for catalytic functions, a heterogeneous photocatalyst delivering both H2 and O2 has not yet been realized. This polymer catalyst design enables the photocatalytic diatomic O2 release, a bottleneck in water splitting, in a facile way. Photocatalytic release of H2 as well as O2 occurs with long-term durability of 20 cycles in 300 days with negligible decrease in efficiency, thus demonstrating the excellent performance of this new catalyst.